(untitled) (Jurnal Sosial Ekonomi Pertanian, 2018)
Abstract The research was conducted in the Village of Laba, District of Masamba, Regency of North Luwu, South Sulawesi in order to determine: 1) The role of sago at the household level to the food diversification; and 2) The level of nutritional adequacy of household. The population of household as much as 533 heads of households and sample as much as 30 households. Determination of the samples was done by simple random sampling method. Sago role analysis in terms of the social aspect is described qualitativey, and to determine the level of nutritional adequacy used food consumption analysis by using Software Nutri Survey.The result showed that 1. The role of sago in terms of the social aspect, although it is still regarded as a traditional food but always served with a variety of various processed sago (kapurung, dange, bagea, sagu lempeng, ongol-ongol, jepa, sinoli, cendol) at both the household and when there are small and big party (celebration, circumcision, aqiqah, weddings). 2. The level of nutritional adequacy of respondents looks at the category level is less. This is because each of the households are different in consumption patterns. Each member of the family in a household there who do not eat processed (sago) with a combination of side dishes the amount that should be. Keywords: the role of sago; diversification of food; supporting nutrition.